Accountability Of Tomangrara Banua Ceremony - Pongsapan, Marchelyn; Purwanti, Lilik (Accounting Department,, 2022)
Purpose—This study aims to analyze and understand the Toraja Tribe's role in conveying accountability at the Mangrara Banua Ceremony. Design/methodology/approach - This study uses a qualitative approach. Data collection was carried out through in-depth semi-structured interviews and the collection of documents related to the implementation of non-cash transactions. The informants in this study involved five participants consisting of Traditional Elders or To Minaa, the Chief Executive of the Mangrara Banua Ceremony, the Treasurer of the Mangrara Banua Ceremony, Religious Figures, and the General Public as well as cultural observers. Findings -Research results show that accountability is described through the philosophy of Tallu Lolona A'pa' Tauninna at the Mangrara Banua Ceremony. This philosophy contains the same meaning as the Tri Hita Karana concept in Balinese society, where three elements cause happiness to be achieved through harmony. In the application of these three elements of happiness at the mangrara banua ceremony, five models of accountability are created, including: 1) Spiritual Accountability, containing the value of piety and faith in the Deata and To Membali Puang as evidence of respect for the pa'rapuan family in the form of a pesung; 2) Economic Accountability, contains a sense of belonging to the house that is being ordained as proof of love and kinship in the form of cash donations, pork and other materials needed to support the success of the mangrara banua ceremony; 3) Social Accountability by respecting the rights of others not only from the same Tongkonan descent but from the outside community, which is manifested in the form of meat distribution; 4) Ecological Accountability, contains the value of gratitude for nature which has provided itself as ingredients for the mangrara banua ceremony which is packaged in the form of pesung and replanting of used plants; and 5) Accountability for Community Mobilization, contains the value of compliance with Government regulations regarding the Covid-19 Pandemic in the form of implementing health protocols to reduce Covid-19 transmission. Practical implications â€“ The implementation of accountability for the Mangrara Banua ceremony found supporting factors that hindered the implementation of accountability policies. This is useful in improving the quality of the mangrara banua ceremony, so that the implementation that is carried out is not limited to fulfilling aluk activities, but also has the use of bringing together all family members that have been far apart for a long time. Originality/value - Implementation of accountability at the mangrara banua ceremony is a necessity for pa'rapuan because it brings many benefits in order to create a stronger kinship between family members. This study seeks to analyze the application of the Toraja culture contained in every activity of the mangrara banua ceremony. This study reveals the facts that occurred related to the implementation of the accountability process, which is packaged in Aluk Todolo's belief so that it shows that in the world of accounting, accountability is not just a matter of financial statements but the existence of other objects in completing it. Keywords - Tallu Lolona A'pa' Tuainna, Spiritual Accountability, Social Accountability, Economic Accountability, Ecological Accountability, and Community Mobilization Accountability. Paper type - ethnography